Some Results on Anti-Invariant Submanifolds of \((LCS)_N\)-Manifold (Journal of Informatics and Mathematical Sciences, 2018)
The object of the present paper is to study anti-invariant submanifolds \(M\) of \((LCS)_{n}\)-manifold \(\bar{M}\). The basic equations are decomposed into horizontal and vertical homomorphisms and geometric properties of anti-invariant submanifolds are studied.
Keywords: Anti-invariant submanifold; \((LCS)_n\)-manifold; Horizontal and vertical projections; Totally umbilical; Totally geodesic